Historical, contemporary, and philosophical-religious perspective on the relationship between religion and morality: Complementarity or contradiction - Pramenković Almir; Pramenković Misala; Nezar Omran (Univerzitetska Misao)
This paper explores the complex relationship between religion and morality from a historical, philosophical, and contemporary perspective. The author shows how moral norms have often been linked to religious beliefs throughout history, from ancient civilizations and medieval Europe to the changes during the Enlightenment. Through three approaches - religion as the basis of morality, morality without religion (a contradictory relationship), and the complementary relationship between them - the paper offers insight into different scientific positions on this topic. Religion is traditionally considered the foundation of moral norms, while Kant based ethics on reason, and Nietzsche criticized religious morality. The paper also analyses how different religions, such as Eastern religions (Hinduism and Buddhism), Judaism, Christianity, and Islam, shape moral values through their teachings. Of course, taking into account the religious background of the author of this text, greater focus is placed on the role of the Islamic perception of morality. Such a position does not at all diminish the scientific value of the text itself. Sociological, philosophical and empirical critiques of religious morality further illuminate the challenges facing morality in modern society, while secular morality, such as Kantian ethics, is considered as an alternative. The synergy of religion and morality undoubtedly leads to better humanization of man and peace in the world. Finally, the author emphasises the role of the Islamic worldview in the transmission of morality and the importance of a multidisciplinary approach to understanding the interaction between religion and morality in the contemporary world.